Does the efficiency of public investment in human capital affect the country’s economic development? - Kozuń-Cieślak, Grażyna (Czy efektywność inwestycji publicznych w kapitał ludzki wpływa na rozwój gospodarczy kraju?, 2020)
Modern theories of economic growth emphasize the meaning of the investment in human capital as the most profitable. Although the positive relationship between public investment in human capital and the country’s economic development is commonly accepted, the answer to the question of whether the efficiency of this investment is crucial for welfare, is no longer so obvious. The aim of this study is to recognize the relationship between the technical efficiency of public spending on human capital and the economic development in the sample of 28 EU states. For this purpose DEA method was applied to evaluate the efficiency of public expenditure on healthcare and education in order to build human capital. Then, DEA scores were correlated with countries’ economic development indicators expressed by GDP per capita. The study proves that the commonly accepted dependency between the potential of human capital and countries’ welfare is not reflected in the correlation between countries’ GDP per capita and the DEA efficiency of public investment in human capital
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 43-54